Isocitrate Dehydrogenase–Mutated Cholangiocarcinoma: Natural History and Clinical Outcomes. (5th January 2022) - Wintheiser, Grant; Zemla, Tyler; Shi, Qian; Tran, Nguyen; Prasai, Kritika; Tella, Sri Harsha; Mody, Kabir; Ahn, Daniel; Borad, Mitesh; Bekaii-Saab, Tanios; Mahipal, Amit
Abstract : Purpose: Clinical-pathologic features and natural history of patients with isocitrate dehydrogenase ( IDH )-mutant intrahepatic cholangiocarcinoma (CCA) are not well characterized. Here, we sought to describe the natural history, clinical phenotype, and prognostic impact of advanced, IDH -mutated CCA. METHODS: We conducted a multicentric, retrospective analysis of patients with IDH -mutated (IDH1 or IDH2) CCA between 2010 and 2020. Median overall survival (OS) and progression-free survival (PFS) analyses were performed using the Kaplan-Meier method. Chi-square test was used to analyze disease control rate (DCR) and overall response rate (ORR). Matched controls were used for comparing survival between patients with and without IDH mutations (mIDH). RESULTS: Sixty-five patients with IDH -mutated CCA were included. All patients had intrahepatic CCA. On first-line chemotherapy, median OS and median PFS were 21.2 months and 8.3 months, respectively. Notably, median OS (32.4 v 19.5 months, P = .12) and PFS (18.0 v 8.0 months, P = .12) were not significantly affected by disease status at presentation (locally advanced v metastatic, respectively). Median OS was significantly longer in patients with mIDH (21.2 v 10.5 months; P < .01). First-line gemcitabine-containing regimens had a significantly higher DCR and ORR than non–gemcitabine-containing regimens (DCR: 75% v 33%, P = .01; ORR: 39% v 0%, P = .02). In patients receiving IDH inhibitor therapy, median PFS was 4.6 months with a DCR of 29%. CONCLUSION: CCA with m IDH confers a unique subtype resulting in a better survival compared with that of counterparts. IDH inhibitors represent a promising therapeutic option in later lines of therapy in this subgroup. Abstract :